Net worth and housing equity in retirement - Todd Sinai; Nicholas S. Souleles (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
This paper documents the trends in the life-cycle profiles of net worth and housing equity between 1983 and 2004. The net worth of older households significantly increased during the housing boom of recent years. However, net worth grew by more than housing equity, in part because other assets also appreciated at the same time. Moreover, the younger elderly offset rising house prices by increasing their housing debt, and used some of the proceeds to invest in other assets. We also consider how much of their housing equity older households can actually tap, using reverse mortgages. This fraction is lower at younger ages, such that young retirees can consume less than half of their housing equity. These results imply that 'consumable' net worth is smaller than standard calculations of net worth.
urn:nbn:de:hebis:30-52340
Keywords: G11; E21; 330; Housing; Home Equity; Retirement; Net Worth; Lebenszyklus; Rentner; Privater Haushalt; Vermögen; Immobilien; Bewertung; USA